Coincident flooding in Queensland : an audit of existing coincident flooding projects - Queensland Climate Change Centre of Excellence; Queensland. Climate Change Centre of Excellence; Queensland. Department of Environment and Resource Management (Brisbane, Qld. : Dept. of Environment and Resource Management, 2012)
The Coincident Flooding in Queensland project has been established in partnership with Emergency Management Queensland (EMQ) to provide more detailed scientific advice on the risk of climate change to coincident flooding in Queensland to inform disaster planning. The project examines the combined effect of riverine flooding and storm tide inundation on flood levels in Queensland. It also considers the impact of climate change on these flood levels. Examples of case studies from Australia and overseas are also considered.
Title from PDF cover page (viewed on September 02, 2013)
February 2012.
Includes bibliographic references (page 35-37)
Also available online (as at 02/09/13) at http://www.longpaddock.qld.gov.au/coastalimpacts/inundation/index.html.
Mode of access. Available online (as at 02/09/13) at http://www.longpaddock.qld.gov.au/coastalimpacts/inundation/index.html.
Keywords: Wind waves -- Queensland; Floods -- Queensland; Floods -- Research -- Queensland; Storm surges -- Queensland; Climatic changes -- Risk assessment